Defining Inclusiveness in Development: Perspective from Local Government’s Apparatus - Widianingsih, Ida; Paskarina, Caroline (Jurnal Bina Praja, 2019)
This article discusses how inclusive development is translated into policy and regional development planning. Perspectives used are that of the regional government apparatus in-charge of development planning. As a strategic actor in decision making, those in charge of development planning hold an important role in determining what counts as inclusive development, who the targets are, and how such inclusivity could be realized through development programs. The research was conducted in Bandung Regency, one of the regions that experience rapid economic growth, as well as one that is facing the challenges of poverty and the decline of environmental support capacity. The method that was used in this research is the quantitative method to discover the perceptions of government apparatus, which afterwards are confirmed through textual analysis of regional development planning documents. From this initial research, development planning process is suspected to not have optimal public participation, as well as to not have involved marginalized groups, so that policies and programs are less able to accommodate several strategic regional issues. Therefore, there is a need to create a comprehensive effort towards achieving an inclusive development agenda as the primary goal in Bandung Regency development.